Crowdfunding : a guide to raising capital on the internet - Dresner, Steven, 1970- (Hoboken : Wiley, 2014)
A groundbreaking book on the growing trend of crowdfunding Crowdfunding has gained considerable traction over the last few years. By combining the Internet/social media with equity-based financing, it is poised to usher in a new asset class that will change how early stage and small business financing transactions are consummated. Author Steven Dresner, Founder and CEO of DealFlow Media, understands the nuances of how crowdfunding can help companies gain much needed access to capital, and now he shares those insights with you. Engaging and informative, this book will serve the n.
The Nuts and Bolts of PatentsCrowdfunding Risks and the Provisional Patent Application; The America Invents Act; Copyright: Protection of Creative Works; Crowdfunding Risks with Copyrightable Material; Trademark: Designations of Source or Origin; Crowdfunding Risks with Trademarks; Trade Secret Protection; Crowdfunding Risks with Trade Secrets; IP Portfolio Management: A Best Practice; Chapter 7: Understanding Your Investor Options; The Decision to Bring on Investors; Benefits; Drawbacks; General Obligations to Investors; Regulatory Obligations; Nonaccredited versus Accredited Investors.
Investor Education Obligations.
Includes bibliographical references and index.
Print version record.
Keywords: Electronic fund raising; Small business -- Finance; New business enterprises -- Finance; Electronic fund raising; Electronic fund raising. Small business -- Finance; New business enterprises -- Finance; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare; SOCIAL SCIENCE -- Human Services; Electronic fund raising; New business enterprises -- Finance; Small business -- Finance; Electronic books